The Effect of Audio-Visual Media on Students' Beginning Reading Ability at Grade I of SDN 091355 Urung Panei - Cintia Floren Malau; Yanti Arasi Sidabutar; Canni Loren Sianturi (International Journal of Technology and Education Research, 2026)
This study aims to determine the effect of audio-visual media on the beginning reading abilities of first-grade students at SD Negeri 091355 Urung Panei. The problem in this study is the students’ low beginning reading abilities, such as difficulty recognizing letters, distinguishing letter sounds, stringing syllables into words, and low student interest and motivation in reading activities. Based on observations, it was found that out of 30 students, only 9 students (30%) obtained a score of ≥70 and were declared to have completed the reading, while 21 students (70%) obtained a score of ≤70 and were declared to have not completed the reading. This study used a quantitative research method with an experimental design using a One Group Pretest-Posttest Design. The study was conducted on first-grade students at Urung Panei Elementary School 091355, with a sample size of 30 students, consisting of 17 boys and 13 girls. Based on the data analysis, the average pretest score was 37.66 and the average posttest score was 87.33. The normality test showed a normally distributed data with a significance value of 0.419 > 0.05. Furthermore, the N-Gain test yielded a value of 0.8147, which is considered high. Therefore, it can be concluded that audiovisual media has an effect on the beginning reading skills of first-grade students at Urung Panei Elementary School 091355.